2001
DOI: 10.1046/j.1365-2664.2001.00607.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of cavity microclimate as a factor influencing selection of maternity roosts by a tree‐dwelling bat, Chalinolobus tuberculatus, in New Zealand

Abstract: Summary1. Cavity quality is important for the productivity and survival of many species of treedwelling wildlife. Intensive land management practices, such as logging and agriculture, frequently reduce cavity availability and potentially affect the long-term viability of populations. 2. The New Zealand long-tailed bat Chalinolobus tuberculatus selects roosts in small knot-hole cavities with specific structural properties relative to available cavities. They also change roosts daily among a large pool of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
169
2
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(191 citation statements)
references
References 68 publications
13
169
2
6
Order By: Relevance
“…The observed preference for tree holes with thick walls and large volumes, both factors that increase the insulation capacities of tree holes (Kunz 1982;Sedgeley 2001;Gibbons & Lindenmayer 2002;Kunz & Lumsden 2003), further supports the hypothesis that thermoregulatory needs are largely responsible for the choice of sleeping site in the study animals. Furthermore, mouse lemurs have only been observed to enter torpor during the dry but not the wet season (Schmid & Speakman 2000).…”
Section: Thermoregulatory Demands and Sleeping Sitessupporting
confidence: 54%
See 3 more Smart Citations
“…The observed preference for tree holes with thick walls and large volumes, both factors that increase the insulation capacities of tree holes (Kunz 1982;Sedgeley 2001;Gibbons & Lindenmayer 2002;Kunz & Lumsden 2003), further supports the hypothesis that thermoregulatory needs are largely responsible for the choice of sleeping site in the study animals. Furthermore, mouse lemurs have only been observed to enter torpor during the dry but not the wet season (Schmid & Speakman 2000).…”
Section: Thermoregulatory Demands and Sleeping Sitessupporting
confidence: 54%
“…Ardia et al 2006;Velky et al 2010). It is well documented that tree holes can buffer against temperature fluctuations (Schmid 1998;Sedgeley 2001;Willis & Brigham 2007;Isaac et al 2008) and the change in sleeping site usage that we observed may thus indicate the lower thermoregulatory constraints experienced by the females during the wet season. During the dry season, the lower minimum temperatures, greater temperature fluctuations and low food availability mean that females must expend more energy to maintain a high body temperature.…”
Section: Thermoregulatory Demands and Sleeping Sitesmentioning
confidence: 61%
See 2 more Smart Citations
“…For the long-tailed bat, which relies mainly on roosting trees (Sedgeley & O'Donnell 1999b), roost quality is lower in pastoral areas compared with that in native forests (Sedgeley & O'Donnell 2004), although the quality of roosts in plantations is currently unquantified and so cannot be compared. Declines in roost quality associated with logging and agriculture are likely to affect bats' reproductive success and survival by increasing energetic costs and diminishing long-term population viability (Sedgeley 2001). Past declines in native fauna, and specifically longtailed bats, have been associated with a reduction in forested habitat (O'Donnell 2000b).…”
Section: Likely Effects Of Reductions In Forested Area On Long-tailedmentioning
confidence: 99%